A Methodological Study of Order Effects in Reporting Relational Aggression Experiences - Serico, Jennifer M. (Journal of interpersonal violence, 2021)
Unlike the overt nature of physical aggression, which lends itself to simpler and more direct methods of investigation, the often-masked nature of relational aggression has led to difficulties and debate regarding the most effective tools of study. Given concerns with the accuracy of third-party relational aggression reports, especially as individuals age, self-report measures may be particularly useful when assessing experiences with relational aggression. However, it is important to recognize validity concerns—in particular, the potential effects of item order presentation—associated with self-report of relational aggression perpetration and victimization. To investigate this issue, surveys were administered and completed by 179 young adults randomly assigned to one of four survey conditions reflecting manipulation of item order. Survey conditions included presentation of (a) perpetration items only, (b) victimization items only, (c) perpetration items followed by victimization items, and (d) victimization items followed by perpetration items. Results revealed that participants reported perpetrating relational aggression significantly more often when asked only about perpetration or when asked about perpetration before victimization, compared with participants who were asked about victimization before perpetration. Item order manipulation did not result in significant differences in self-reported victimization experiences. Results of this study indicate a need for greater consideration of item order when conducting research using self-report data and the importance of additional investigation into which form of item presentation elicits the most accurate self-report information.